Perkembangan Moral Karakter Jin Sakai dalam Game Ghost of Tsushima Berdasarkan Teori Lawrence Kohlberg - Vanady, Michael; Wahyuningsih, Tri Mulyani (KIRYOKU, 2025)
This study aims to analyze the moral development of the main character Jin Sakai in the video game Ghost of Tsushima using Lawrence Kohlberg's moral development theory. Ghost of Tsushima is an action-adventure game by Sucker Punch Productions released in 2020. The main data of this study is the narrative of the Ghost of Tsushima game, including the storyline, dialogue, and moral choices of the main character. A qualitative approach and descriptive method were used to explore the narrative, dialogue, and moral choices made by the characters in the game. Data were collected through observations of relevant cutscenes and gameplay, then analyzed using Kohlberg's six stages of moral development. The results showed that Jin Sakai underwent a complex moral transformation, starting from the preconventional phase of the legal and obedience orientation stage, the instrumental-relativist orientation stage, then entering the conventional phase of the interpersonal agreement orientation stage, the law and order orientation stage, until reaching the postconventional phase of the social contract orientation stage, and the universal ethical principles stage. This change is reflected through the inner conflict between maintaining the honor of the samurai and saving the people from the Mongol invasion in new ways that Jin Sakai created himself. These findings show that interactive media such as video games not only offer entertainment, but are also able to represent deep and relevant moral dynamics in the context of learning ethics and reflecting on human values in the digital era.